Video ethnography in practice: planning, shooting and editing for social analysis - Shrum, Wesley (Sage, 2017)
Video Ethnography in Practice is a brief guide for students in the social disciplines who are required to produce an ethnographic video, the most significant new methodological technique in 21st century social analysis. The authors, both accomplished videographers, cover the basic techniques of creating a video that documents human culture and behavior with true stories of the process of videography throughout. This text shows how new technologies like smart phones, widely available video editing software, and YouTube, have turned video ethnography into something that is within reach of students in a conventional course framework.